‘Temporary Workers’, Temporary Fathers: Transnational Family Impacts of Canada’s Seasonal Agricultural Worker Program - McLaughlin, Janet; Wells, Don; Mendiburo, Aaraón; Lyn, André; Vasilevska, Biljana (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2017)
SummaryUnder Canada’s Seasonal Agricultural Worker Program (SAWP), migrant workers come to Canada for up to eight months each year, without their families, to work as temporary foreign workers in agriculture. Using a ‘whole worker’ industrial relations approach, which emphasizes intersections among work, family and community relations, this article assesses the impacts of these repeated separations on the wellbeing and cohesion of Mexican workers’ transnational families. The analysis is based primarily on 74 in-depth, semi-structured interviews that were conducted in Spanish with male workers, their spouses and children, and with the children’s teachers. Assessment criteria include effects on children’s health and educational success, children’s behaviour, mothers’ abilities to cope with added roles and work, and emotional relations among workers, children and spouses.The study findings suggest that families are often negatively impacted by these repeated separations, with particular consequences for the mental and physical health of children. Children’s behavioural challenges often include poor school performance, involvement in crime, drug and alcohol abuse (especially among sons), and early pregnancies among daughters. As temporary ‘single moms,’ wives often have difficulty coping with extra functions and burdens, and lack of support when their husbands are working in Canada. Typically, there are profound emotional consequences for workers and, frequently, strained family relations. The article concludes by offering practical policy recommendations to lessen negative impacts on SAWP workers and their families, including higher remittances; improved access to labour rights and standards; and new options for family reunification.